Determinants of airborne rat and mouse urinary allergen exposure - Hollander, A.; Heederik, Dick; Doekes, G.; Kromhout, Hans (Scandinavian Journal of Work, Environment & Health, 1998)
' ' OBJECTIVES ': 'The purpose of this study was to determine the factors affecting exposure to rat and mouse urinary allergens.' ' METHODS ': 'Ambient and personal air sampling was performed on a large scale in 7 laboratory animal facilities.' ' RESULTS ': 'Allergens were mainly present as large particles (5.8 mm). The higher the number of animals in a room, the higher the allergen concentrations. Allergen levels were twice as high on Mondays as on other days due to the tasks performed on Mondays. Filter tops on animal cages were associated with 6-17 times lower ambient allergen levels. An inverse day-night rhythm for rats produced ³10 times higher rat urinary allergen levels. Personal exposure to rat and mouse urinary allergens differed between job titles but especially between facilities, probably because of differences in task performance and technology. Task-specific sampling revealed that the highest personal exposure levels occurred when contaminated bedding and high numbers of conscious animals were handled. The proportion of time spent on these tasks determined the degree of allergen exposure to a large extent.' ' CONCLUSION ': 'This study showed that the number of animals present in the room, use of filter top cages, and an inverse day-night rhythm were important determinants of rat and mouse urinary allergens in ambient air. Personal exposure to rat and mouse urinary allergens was predominantly determined by the task and site and, to a limited extent, by ambient exposure levels. The presented determinants can be used to develop exposure reduction strategies and also to aid epidemiologic studies of laboratory animal allergy.
Keywords: aeroallergens; ambient air; job title; laboratory animal; task